Regional Development And Railways In Peru: 1850-1819 - Pennano, Guido (1979)
When discussing serious problems of underdevelopment, it is discovered, as very important elements to break the barrier of backwardness, the integration national integration and articulation. The phenomenon of national integration and its conversion into a true nation-state requires, in most cases, the contribution of a system of effective communications and transport, without which the possibility of internal articulation becomes remote. Failure to achieve this interaction of different geographic-productive in the country, instead of an articulated country there will be a society torn apart, in which the constituent most striking is the “heterogeneous underdevelopment”: that is, a society shaped by areas poorly integrated with each other, where the common element between them will be given by the interaction of them to the metropolis to which they have undergone, and not because of their belonging to a society defined territorially and politically. The common characteristics will be based on the mode of production that was imposed at different times or historical instances of the advance of the dominant system and the effects that this forced articulation produces.